Lustro, rozstanie i miłość – o "Banicie" Jana Brzechwy - Urbańska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Mirror is on the top of a list of things with deep cognitive sense. It is the instrument of truth and self-recognition. Mirror has also constructive sense – destroys hitherto existing order of the world to initiate a new hierarchy of value. In Brzechwa’s poetry mirror exists as a turning point as well. Brzechwa’s jilted lover (outlow) seeks in a foggy mirror his reflection, he tries to find his new identity in the new tragic situation. He also looks for any proofs of his existence. Misty mirror reflects mental condition of lost man. In the study we will discuss the problem.